Ferroelectric Bi3.25La0.75Ti3O12 photodiode for solar cell applications - Yakuphanoğlu, Fahrettin; Tataroglu, A.; Al-Ghamdi, Ahmed A.; Gupta, R. K.; Al-Turki, Yusuf; Serbetci, Z.; El-Tantawy, Farid (Elsevier, 2015)
Bi3.25La0.75Ti3O12 thin film was prepared on p-type silicon substrate by sol-gel spin coating method. The film indicates a ferroelectric behavior with a remanent polarization of similar to 18.2 mu C/cm(2). Electronic parameters such as ideality factor and barrier height of the diode were calculated to be 3.80 and 0.75 eV, respectively. The photocurrent results in the reverse bias of the diode indicate that photocurrent under illumination is higher than the dark current. The diode exhibited a substantial visible-light photovoltaic effect. The capacitance-voltage and conductance-voltage measurements were carried out in the frequency range of 10 kHz-1 MHz. The observed decrease in the capacitance and increase in the conductance with the increasing frequency were explained on the basis of interface states. The interface states density of the structure was determined using Hill-Coleman method and observed to decrease with increasing frequency. The obtained results indicate that ferroelectric Bi3.25La0.75Ti3O12/P-type silicon junction is a new class of photoconductive devices with low-cost fabrication and high photoresponsivity. (C) 2014 Published by Elsevier B.V.
Keywords: Bi3.25La0.75Ti3O12 thin film; Sol-gel method; Electrical properties; Frequency dependence